Effect of Commitment, Internal Audit, and Financial Management on Local Government Performance in South Sumatra - Negara, I. G. B Surya; Susetyo, Didik; Kadir, Syamsurijal Abdul; Yuliana, Saadah (International Journal of Economics and Financial Issues, 2018)
This study aims to determine the effect of affective commitment, continuance commitment, normative commitment, internal control of income accounting system, internal control of expenditure/cost accounting system, budget planning, budget implementation, reporting and budget accountability, budget performance evaluation on local government performance in South Sumatera. The analysis used primary data and secondary data with analysis technique using multiple linear regression. The result of this research concludes that affective commitment has a significant and positive effect on local government performance and internal control of income accounting system has negative and significant influence to local government performance, while other variables have no effect. The estimation results also show that the regencies of Empat Lawang, Prabumulih and Ogan Komering Ilir are better, while the Ogan Komering Ulu Timur, Lubuk Linggau and Lahat districts are lower. The financial performance of local government which is categorized as very effective is OKI Regency and OKUT, efficient category is OI Regency, OKUS, OKUT, OKI, OKU, Empat Lawang, and very economical is Muratara Regency. Keywords: commitment, internal control, financial management, performance, local government JEL Classifications: G18, C33, O18.